Animal Control and Field Services Officers’ Perspectives on Community Engagement: A Qualitative Phenomenology Study - Liana R. Moss; Sloane M. Hawes; Katherine Connolly; Morgan Bergstrom; Kaleigh O’Reilly; Kevin N. Morris (Animals, 2022)
Very little is known about the prevalence, scope, and methods of community engagement employed by animal control and field services officers to address the issue of animal cruelty and neglect. This study used a phenomenological approach to understand how officers defined community engagement. The researchers conducted semi-structured interviews with twenty-nine animal control and field services officers. The definitions of community engagement varied greatly across this sample of U.S. officers. However, most officers agreed that strategies such as relationship-building, providing assistance or information, and allowing time for compliance were among the most effective community engagement strategies. In addition, several barriers to incorporating community engagement strategies in the work of animal control professionals were identified. Future research and policymaking should seek to establish a consistent definition of community engagement in animal control and field services that can then be optimized for specific communities through rigorous evaluation.